2023
DOI: 10.1007/s10862-023-10059-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Psychopathic Traits Early in Development: Testing Potential Associations with Social, Behavioral, and Affective Factors

Abstract: The Child Problematic Traits Inventory (CPTI) enables the assessment of psychopathy dimensions as early as age three. The current study employs a multi-informant approach (i.e., fathers, mothers, and teachers) to further investigate the unique associations between psychopathy dimensions, as measured by the CPTI, with theoretically relevant constructs of interest, such as conduct problems, oppositionality, empathy, and social relations, in early childhood (N = 1283, M age = 6.35). Although associations with con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 91 publications
0
1
0
Order By: Relevance
“…Furthermore, based on the results of multiple regression the relationship between the teacher interaction questionnaire and learning outcomes explains that the scale of the questionnaire varies from not very significant in predicting learning outcomes in the cognitive, affective, and moral domains of students (Rose et al, 2023;Scherzinger & Wettstein, 2019). Positive teacher interaction questionnaire scales such as leadership, helpfulness/friendliness, understanding, responsibility/freedom not only act as significant predictors of learning outcomes, but also tend to show a positive relationship with learning outcomes in every aspect (Bajovic & Rizzo, 2021;Demetriou et al, 2023). This is different from the negative interaction questionnaire scale which does not have a significant impact on student learning outcomes in all aspects of student learning outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, based on the results of multiple regression the relationship between the teacher interaction questionnaire and learning outcomes explains that the scale of the questionnaire varies from not very significant in predicting learning outcomes in the cognitive, affective, and moral domains of students (Rose et al, 2023;Scherzinger & Wettstein, 2019). Positive teacher interaction questionnaire scales such as leadership, helpfulness/friendliness, understanding, responsibility/freedom not only act as significant predictors of learning outcomes, but also tend to show a positive relationship with learning outcomes in every aspect (Bajovic & Rizzo, 2021;Demetriou et al, 2023). This is different from the negative interaction questionnaire scale which does not have a significant impact on student learning outcomes in all aspects of student learning outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a simpler questionnaire was developed in America and Australia using a Likert scale and a question range of 50-60 questions. Since then, this questionnaire has been developed by several countries including countries in the Asian region, such as Japan, Korea and Singapore (Demetriou et al, 2023;Sun et al, 2018). In addition, several previous studies have also confirmed the reliability and validity of the teacher interaction questionnaire.…”
Section: Introductionmentioning
confidence: 93%
“…Specifically, adolescents with elevated CU traits tend to report diminished subjective fear when recalling emotionally charged life events [16], score lower on self-report fear assessments [17], exhibit reduced physiological arousal to emotional stimuli [18], and demonstrate lower awareness of behaviors that elicit fear in others [19]. The low fear response has been attributed to deficits in emotional processing and the ability to see others' perspectives [20]. Given that this fear deficit has been observed among preschoolers [21], fearlessness can exacerbate typical social development and play a bidirectional role in the development of CU traits [22].…”
Section: Fear and Cu Traitsmentioning
confidence: 99%